2020
DOI: 10.3390/ijms21176056
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Response to Dental Implant: Comparison Study on the Effects of New Nanopored Laser-Treated vs. Traditional Healing Abutments

Abstract: The health of peri-implant soft tissues is important for the long-term success rate of dental implants and the surface topography is pivotal in influencing it. Thus, the aim of this study was to evaluate, in human patients, the inflammatory mucosal microenvironment in the tissue surrounding a new, nanoscale, laser-treated healing abutment characterized by engineered nanopores versus a standard machined-surface. Analyses of anti- and pro-inflammatory markers, cytokeratins, desmosomal proteins and scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…5,182 Clinical investigations are lacking and are needed to verify the effect of abutment surface treatment on the soft tissue seal, which safeguards the implant from bacterial invasion and periimplantitis. 202 Please do not adjust margins Please do not adjust margins…”
Section: Abutment Dis-/re-connectionmentioning
confidence: 99%
See 4 more Smart Citations
“…5,182 Clinical investigations are lacking and are needed to verify the effect of abutment surface treatment on the soft tissue seal, which safeguards the implant from bacterial invasion and periimplantitis. 202 Please do not adjust margins Please do not adjust margins…”
Section: Abutment Dis-/re-connectionmentioning
confidence: 99%
“…Micro-and nanotechnology have been applied to the transmucosal surface of the abutment to enhance the soft tissue seal. 161,201,202 Various surface treatments can alter the surface topography or characteristics, including machining, blasting, plasma spraying, chemical or electrochemical etching, laser treatment, and others. 161 Some animal studies revealed higher attachment of connective tissue on a laser-grooved Ti abutment, when compared to the turned smooth-surfaced Ti abutment.…”
Section: Importance Of Abutments In the Soft Tissue Sealmentioning
confidence: 99%
See 3 more Smart Citations